(3OQGSI JbjjejI deSGQGJ GdJfejI MGdI GdLRGFQs - (3eSYhO(B, (3ejghHs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdGTgGQ(B,s, 2023)
(3jMJhj gPG GdcJGH Ydi KdGK aUhd GVGaI Edi GdaUd GdJegjOj, eONd Edi GdSjGSGJ GdEbJUGOjI GdcdjI hGdGSJbQGQ GdEbJUGOj Gdcdj, HeG ajg GdGWGQ GdeaGgjej ddSjGSI GdEbJUGOjI GdcdjI,eY JMbjb efXheI GdGSJbQGQ GdGbJUGOj Gdcdj,, cPdc COhGJ GdSjGSI GdGbJUGOjI GdcdjI, hHYOgG JMOK Yf eMOOGJ GdGSJbQGQ GdGbJUGOj Gdcdj aj Xd GdfXQjI GdGbJUGOjIGVGaI Edi JMdjd GdhbGFY dSdhc eDTQGJ GdGSJbQGQ GdeGdj Gdcdj aj GdLRGFQ, hCNjQG eMOOGJ GdGSJbQGQ GdEbJUGOj Gdcdj ef efXhQ COhGJ GdbjGS GdEbJUGOj(B.s
(3eQGLY U(B.294 s
Keywords: (3GdESJbQGQ GdEbJUGOjs; (3Gdfeh GdEbJUGOjs